Vivre et écrire dans l’odeur de la mort (“L’Afrique au-delà du miroir” et “Murambi, le livre des ossements” de Boubacar Boris Diop) (Altre Modernità, 2010)
The essay provides an analysis of the emotional and intellectual experience lived by the Senegalese novestist Boubacar Boris Diop in Rwanda in 1998, when he, among other writers, was involved in the initiative "écrire par devoir de mémoire", an initiative aiming at reflecting upon the terrible events of the 1994 genocide.In his collection of essays, L'Afrique au-delà du miroir, Boubacar Boris Diop offers an intense reflection upon this experience which also iaugurated for him a new conception of history and a new notion of literary writing. As a testimony of this change, the novel Murambi, le livre des ossements reads like a funerary monument to celebrate the memory of the hundreds of thousands of Tutsi people  massacred during the genocide.
Keywords: romanzo; Boubacar Boris Diop; genocidio; Rwanda